The Role of Media Materials in French Language Learning: A Case Study: A Case Study (Teacher’s World: Journal of Education and Research, 2024)
The importance of media in language learning is covered in this article. The goal is to identify the media that students find engaging and how it advances or enhances their learning process. The development of the French language among students has increased, as this article will demonstrate, particularly for those who regularly consume media on TV and other platforms like YouTube, Netflix, etc. A survey was conducted among the students of the department of French Language & Culture at the Institute of Modern languages, Dhaka University. There are 50 French learners who have participated in this study are the students of French Language & Culture, IML, International Relations, Dhaka University and the students of BUP. Through this study, a survey based on a quantitative data was conducted by distributing a set of questionnaires to the participants. An impressive impact on learning French is seen when data collected from participants is analyzed along with their ideas. This definitely helps to accelerate the learning process. Ultimately, some recommendations on how to choose suitable media resources to enhance the course's relevance and effectiveness will be given.Teacher’s World: Journal of Education and Research, 49 (2),75-84